Effects of substrate surface roughness and aluminizing agent composition on the aluminide coatings by low-temperature pack cementation. (12th December 2018) - Dong, Jian; Sun, Yanhui; He, Feiyu; Huang, Hongtao; Zhen, Jianping
Abstract: In this study, a new low-temperature aluminizing process combining surface slurry pre-coating at room temperature with pack cementation process was used to prepare the iron-aluminum alloy coating. The effects of different substrate surface roughness and aluminizing agent composition on the coating surface roughness, phase structure and the thickness of each phase in the coating were studied. The results showed that the average surface roughness of the coating with 2000# substrate and 5% AlCl3 was 2.641 μ m. The aluminide coatings under different experimental parameters had the same Fe3 Al, FeAl, Fe2 Al5 and FeAl3 phase structure. However, the thicknesses of Fe3 Al, FeAl and FeAl3 phase layers decreased with the increase of AlCl3 content. Furthermore, the aluminide coating with 2000# substrate and 5% AlCl3 had a bonding strength of 67.60 MPa and outstanding thermal shock resistance. The excellent properties of the iron-aluminum alloy coating made it possible to prepare the top coat on it.